Perioperative diabetes insipidus: Report of two unusual cases - Nissar Shaikh (11659441) (2022)
Diabetes insipidus (DI) is a rare clinical condition in the postoperative period. Post-surgery polyuria is a common finding, as the body excretes the excessive fluid given during surgery. It is important to diagnose and differentiate the DI from post-operative polyuria, as DI can lead to severe dehydration and electrolyte disturbances. We report two unusual cases of perioperative DI requiring desmopressin therapy. Case 1 A 46-year-old healthy male patient developed intraoperative DI leading to hypernatremia during the anterior cervical discectomy and fusion. Anesthesia was maintained with propofol and remifentanil target-controlled infusion (TCI). After two hours of surgery, the patient became polyuric and was passing diluted urine. He received desmopressin and hydration. The patient recovered and was transferred to the ward, then, discharged home without any clinical or neurological problems. Case 2 A 36-year-old healthy male patient underwent elective 3rd ventricular cyst excision. Pre-anesthesia assessment did not reveal any comorbidities and the surgery was uneventful. His anesthesia was maintained with propofol and remifentanil TCI (target-controlled infusion). In the postoperative period, he developed DI requiring hydration and desmopressin. The patient's further recovery was uneventful. He was discharged home through the ward. Conclusion The occurrence of DI in the above-mentioned surgeries is very rare. Both surgical procedures and anesthesia medications can cause perioperative DI. Other Information Published in: Journal of Clinical and Translational Endocrinology: Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jecr.2022.100121